Efficient Management of Soil Moisture with Jute Non-woven as Mulch for Cultivation of Sweetlime and Turmeric in Red Lateritic Zone - Nag, D; Choudhury, T K; Debnath, S; Ganguly, P K; Ghosh, S K (Journal of Agricultural Engineering, 2008)
Mulch is a layer of material spread on top of the soil to conserve soil moisture, discourage the growth of weeds, help prevent erosion and prevent large fluctuations in soil temperature. Mulch modifies the soil micro-climate around the growing plants. Jute geotextile being a woven/non-woven knitted structure of natural fibre is used in various geo-technical, civil engineering and soil conservation applications. It can be used where vegetation is considered to be the long term answer to protected cultivation of fruits and spices in arid and semi-arid regions. With this objective in mind, field trials were undertaken on the use of jute non-woven geo-textiles as mulch for cultivation of sweet lime with turmeric as an intercrop in the dry lateritic soil of Midnapore (West) district of West Bengal. It was observed that yields of sweet lime and turmeric were substantially higher fetching higher economic returns to the growers.